Clinical Presentation of Patients with Hepatocellular Carcinoma in Tertiary level Hospital of Bangladesh (Bangladesh Medical Journal, 2024)
Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer, accounting for 75% - 86% of all cases. Men are affected approximately two to three times more than women. It is considered as the fifth most common cancer in men and the ninth in women. The prognosis for liver cancer is very poor which has made it globally the second most common cause of death from cancer. The highest liver cancer rates are found in East and Southeast Asia and in Middle and Western Africa. Western world is complaining of rising HCC prevalence as a result of migration from HBV-endemic regions, hepatitis C virus (HCV) infection, alcoholic cirrhosis, and non-alcoholic steatohepatitis associated with the obesity epidemics. The accurate diagnosis of HCC dependent on clinical presentation, biochemical, imaging, cytological and/ or histopathological examination. This was a descriptive study of hepatocellular carcinoma patients those attended Dhaka Medical College Hospital and Shaheed Suhrawardy Medical College Hospital, Dhaka, Bangladesh from September 2006 to march 2008. Thirty (30) consecutive biopsy proven hepatocellular carcinoma patients were enrolled in this study. This study collected data by reviewing Medical records (prescriptions and diagnostic reports) and interviewing patients for various present symptoms/ signs, past complaints (symptoms/ signs) they experienced in different duration and for confirmation of HCC. Among the symptoms almost all 29(96.66%) of the patients had experienced loss of appetite and most of the patients were experienced generalized weakness 28(93.33%) followed by weight loss 24(80%). More than two-third of the patients had complained abdominal pain 22(73.33%), abdominal fullness 21(70%), abdominal mass 20(66.66%) and nausea and vomiting 20(66.66%). Various signs of HCC were found in examination during interview and from their past experience/ reviewing medical record of illness; where most of them 27(90%) had hepatomegaly and half of them 15(50%) had splenomegaly and ascites. Among the others sign of HCC, one-third (33.33%) of them had yellow discolouration of eyes, yellowish urine, jaundice and fever. Several signs were also observed like Leg swelling 9(30%), cough 8(26.66%), alteration of bowel habit 6(20%). Signs like blood vomiting 1(3.33%) and leg oedema 4(13.33%) were also observed. Information regarding clinical presentation from this study may be utilized as indicator for referral, case definition in research works and probable diagnosis of HCC. This clinical presentation may be a strong tool for symptomatic surveillance of HCC and prevention of HCC including chronic hepatitis B and chronic hepatitis C virus infection.Bangladesh Med J. 2023 Sept; 52(3): 8-13